Asymptotic behavior of strong solutions of a simplified energy-transport model with general conductivity. (June 2021) - Kim, Yong-Ho; Ra, Sungjin; Kim, Se-Chol
Abstract: In this paper we study a simplified transient energy-transport model in semiconductors with a general conductivity and the Dirichlet boundary conditions on an interval. By using a new iterative scheme, we prove the global existence and uniqueness of strong solutions provided that the variation of the temperature is small. Also, the existence and stability of stationary solutions are proved if the temperature is large.